1997
DOI: 10.1094/pdis.1997.81.4.374
|View full text |Cite
|
Sign up to set email alerts
|

Chayote Mosaic, a New Disease in Sechium edule Caused by a Tymovirus

Abstract: A sap-transmissible virus was isolated from chayote (Sechium edule) in Costa Rica. Infected plants showed chlorotic spots and rings, and blotchy mosaics, which often coalesced to give a complete mosaic and leaf deformation. By electron microscopy, spherical virus-like particles of approximately 29 nm in diameter were visible, and cytological changes associated with the chloroplasts were observed. The virus particles sedimented in sucrose density gradients as two components, a top component of empty protein she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Pepper plants inoculated with field plants identified as 20.5, and 20.8 developed a systemic mosaic, and were the source for the isolation and characterisation of isolates Tula 20.5 and Tula 20.8. Tymovirus-like virions were purified as described by Hord et al [17], and disrupted in 4% sodium dodecyl sulfate, 0.1 M Tris-HCl, pH 9.0, with bentonite at 1 mg/ml, and virion RNA extracted with phenol-chloroform. Virion RNA was used for the biological and genetic characterization of the two isolates.…”
Section: Virus Isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pepper plants inoculated with field plants identified as 20.5, and 20.8 developed a systemic mosaic, and were the source for the isolation and characterisation of isolates Tula 20.5 and Tula 20.8. Tymovirus-like virions were purified as described by Hord et al [17], and disrupted in 4% sodium dodecyl sulfate, 0.1 M Tris-HCl, pH 9.0, with bentonite at 1 mg/ml, and virion RNA extracted with phenol-chloroform. Virion RNA was used for the biological and genetic characterization of the two isolates.…”
Section: Virus Isolatesmentioning
confidence: 99%
“…These results indicated that a virus isolate was transferred from each chiltepin plant to pepper, and that these isolates belonged to the genus Tymovirus. These isolates were named Tula 20.5 and Tula 20.8, and their virions were purified for further characterisation according to Hord et al [17] procedure.…”
Section: Isolation Of a Tymovirus From Wild Chiltepin Plantsmentioning
confidence: 99%
“…However, commercial production of chayote is important in several countries, including Costa Rica, Mexico, Brazil, and Puerto Rico (Lira 1996;Hord et al 1997) where fruit commercialization and export represent a significant source of revenue.…”
Section: Introductionmentioning
confidence: 99%
“…Costa Rica has become the leading exporter of chayote (Lira 1996;Hord et al 1997). In this country, vegetative propagation has been extensively used to produce uniform fruits that fulfill the requirements of the international market (Newstrom 1989;Lira 1996;Hord et al 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation